2018
DOI: 10.1002/lary.27305
|View full text |Cite
|
Sign up to set email alerts
|

Depth of invasion in superficial oral tongue carcinoma quantified using intraoral ultrasonography

Abstract: Objective Depth of invasion (DOI) in oral carcinoma has been integrated into the primary tumor categories in the current tumor‐node‐metastasis staging (8th edition). However, there is no standard modality to determine DOI preoperatively. The aims of the present study were to evaluate the accuracy of a preoperative measurement of DOI using ultrasonography (US) for superficial oral tongue carcinomas, and to correlate the values obtained with histologically determined DOI measurements. Methods We retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 21 publications
3
55
0
Order By: Relevance
“…The articles were published over a period of 17 years (2001-2018), and patient recruitment covered the period 1997-2016. The studies showed a wide geographical distribution, but also, for intraoral US, the most substantial contributions came from Asian countries, in particular, from Japan (six studies) (28,31,33,35,37,38). There was a moderate male preponderance (59%) among the participants included in this analysis.…”
Section: Characteristics Of Intraoral Us Included Studiesmentioning
confidence: 86%
See 4 more Smart Citations
“…The articles were published over a period of 17 years (2001-2018), and patient recruitment covered the period 1997-2016. The studies showed a wide geographical distribution, but also, for intraoral US, the most substantial contributions came from Asian countries, in particular, from Japan (six studies) (28,31,33,35,37,38). There was a moderate male preponderance (59%) among the participants included in this analysis.…”
Section: Characteristics Of Intraoral Us Included Studiesmentioning
confidence: 86%
“…All studies compared TT or DOI measured preoperatively or intraoperatively by intraoral US with TT or DOI measured on histopathological slides. A total of 12 studies (n = 520 patients) was included (19,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). The sample size ranged from 13 to 109 patients.…”
Section: Characteristics Of Intraoral Us Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations